2009
DOI: 10.1002/jor.20567
|View full text |Cite
|
Sign up to set email alerts
|

The fate of transplanted xenogeneic bone marrow‐derived stem cells in rat intervertebral discs

Abstract: Intervertebral disc degeneration is a major cause and a risk factor for chronic low back pain. The potential of using stem cells to treat disc degeneration has been raised. The aims of our study were to assess whether xenogeneic bone-marrow derived stem cells could survive in a rat disc degeneration model and to determine which cell types, if any, survived and differentiated into disc-like cells. Human bone-marrow derived CD34 þ (hematopoietic progenitor cells) and CD34 À (nonhematopoietic progenitor cells, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 42 publications
5
47
0
2
Order By: Relevance
“…Mean ± SD is shown. *P \ 0.05 versus day 0; **P \ 0.005 versus day 0 corroborates studies of others who found transplanted human MSCs to be detectable at 42 days in a xenogenic rat model [55] or in a xenogenic minipig model even after 6 months [27]. Sakai et al used gene transfer of green fluorescent protein (GFP) for cell detection, and thus a convincing cell labeling technique found, that GFP-positive MSCs were detected in the nucleus from 2 to 48 weeks post-transplantation; these cells increased proportionally over time, suggesting that some of the cells had survived and proliferated [48].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Mean ± SD is shown. *P \ 0.05 versus day 0; **P \ 0.005 versus day 0 corroborates studies of others who found transplanted human MSCs to be detectable at 42 days in a xenogenic rat model [55] or in a xenogenic minipig model even after 6 months [27]. Sakai et al used gene transfer of green fluorescent protein (GFP) for cell detection, and thus a convincing cell labeling technique found, that GFP-positive MSCs were detected in the nucleus from 2 to 48 weeks post-transplantation; these cells increased proportionally over time, suggesting that some of the cells had survived and proliferated [48].…”
Section: Discussionsupporting
confidence: 87%
“…Although xenogenic studies showed that human mRNA signals and co-localization of matrix proteins with implanted cells were retained at 6 weeks [55] or 6 months [27] after implantation, neither study addressed the question of implantation efficiency, implant retainment, or quantity of remaining anabolic active cells. Thus, we can only speculate, how much of the initially transferred cells contributed to the reported results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,10,16,20,22,25,[30][31][32][34][35][36][37][38]46,48,49,53,54,56,57,60,62,[64][65][66][67]69,73,83,90 The EuroDISC study, by Meisel and colleagues, 49 investigated the percutaneous transplantation of autologous disc chondrocytes. Following microdiscectomy, disc chondrocytes were harvested and expanded in vitro and were subsequently injected into the NP 3 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple preclinical animal studies have demonstrated the efficacy of intradiscally injected mesenchymal stem cells (MSCs) to induce disc regeneration. 1,2,16,18,20,21,25,[31][32][33][34]38,39,49,53,56,60,[64][65][66]69,73,83,87,90 Allogeneic mesenchymal progenitor cells (MPCs) are the earliest uncommitted clonogenic population of bone marrow stromal cells and have also successfully repaired the extracellular matrix following their injection into degenerative ovine discs. 25 Moreover, when ovine MPCs combined with the chondrogenic agent pentosan polysulfate (PPS) were embedded in a gelatin sponge and placed in a biodegradable cage that was implanted into the interbody space of ovine cervical spines, the cage became filled with a predominately cartilaginous matrix.…”
mentioning
confidence: 99%